2021
DOI: 10.1002/pssr.202100189
|View full text |Cite
|
Sign up to set email alerts
|

Partial Auxeticity of Laterally Compressed Carbon Nanotube Bundles

Abstract: Carbon nanotubes (CNTs) have attracted increasing attention because of their enormous potential in various technologies. Herein, the evolution of the structure and elastic properties of a CNT bundle under compression in uniaxial and biaxial regimes is analyzed using a chain model with a reduced number of degrees of freedom. The compression stress–strain curves consist of four stages, each of which is characterized by a specific structure and deformation mechanism. In the first stage, all CNTs have the same cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 100 publications
(162 reference statements)
0
2
0
Order By: Relevance
“…Novel fabrics with auxetic properties [28,29,30,31], targeted for personal applications have been developed. Alongside the experimental studies, new theoretical models exhibiting negative Poisson's ratio [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] have been proposed. The search for the negative Poisson's ratio in known and naturally occurring materials revealed that around 70% of metals with cubic symmetry have such properties [47].…”
Section: Introductionmentioning
confidence: 99%
“…Novel fabrics with auxetic properties [28,29,30,31], targeted for personal applications have been developed. Alongside the experimental studies, new theoretical models exhibiting negative Poisson's ratio [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] have been proposed. The search for the negative Poisson's ratio in known and naturally occurring materials revealed that around 70% of metals with cubic symmetry have such properties [47].…”
Section: Introductionmentioning
confidence: 99%
“…The present work not only reveals chiral-dependent insights of mechanical properties of SWCNTs, but also first discovered the auxetic phenomenon of perfect SWCNT. It is believed that with these new findings, our work will contribute to future study and application of SWCNTs [45,46].…”
Section: Introductionmentioning
confidence: 66%
“…[19,20] In this work, we use the more recent classification [20] which distinguishes between nonauxetics, partial auxetics, and auxetics. Vast potential applications of auxetic materials drive the theoretical and experimental investigations, which branch into auxetic metamaterials, [21][22][23][24][25][26][27][28] models, [16,[29][30][31][32][33][34][35][36][37][38][39][40][41] structures, [42][43][44][45][46][47][48] polymers, [49,50] composites, [51] foams, [52][53][54] and fabrics. [55][56][57][58] Most of the research on auxetics is focused either on developing new materials or searching for auxetic properties in existing ones.…”
Section: Introductionmentioning
confidence: 99%